Cultural characteristics, morphology, and variation within Claviceps africana and C. sorghi from India - Muthusubramanian, V.; Bandyopadhyay, Ranajit; Rajaram Reddy, D.; Tooley, P. (Elsevier, 2006)
Sorghum ergot in India is caused by Claviceps africana and C. sorghi. The distributions of these two species in India is not known. Eighty-nine sorghum ergot isolates were cultured from young sphacelia obtained from male sterile sorghum plants artificially inoculated using inoculum collected in the field. Based on cultural characteristics, the isolates were separated into two groups which differed distinctly in the morphology of their sphacelia, conidia, and sclerotia. Marked differences also were observed in rates of secondary conidial production and disease spread between the groups. In combination with molecular evidence, our results confirm that the isolates placed in Group I represent C. africana and Group II isolates represent C. sorghi. C. africana was found to be widely distributed in all sorghum growing areas of India. The species first described as occuring in India, C. sorghi, appears to be restricted to a few locations in the states of Maharashtra, Andhra Pradesh, and Karnataka.